2022
DOI: 10.1186/s12875-022-01786-9
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of the primary health care system – German primary care practitioners’ perspectives during the early COVID-19 pandemic

Abstract: Background Primary care is a relevant pillar in managing not only individual, but also societal medical crises. The COVID-19 pandemic has demanded a rapid response from primary care with interventions in the health care system. The aim of this paper was to explore the responses of primary care practitioners (PCP) during the early COVID-19 pandemic and to analyze these with a view on the resilience of the primary health care system from the PCPs perspective. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 38 publications
4
30
0
Order By: Relevance
“…The degree of changes adopted by GP practices across countries indicates a strong ability to adapt, as confirmed in other studies [ 30 ]. However, as our data also showed, there was great variability in the speed and scope of the responses to the impact of COVID-19 in the practices, indicating potentially variable standards and quality of care [ 31 ].…”
Section: Discussionsupporting
confidence: 75%
“…The degree of changes adopted by GP practices across countries indicates a strong ability to adapt, as confirmed in other studies [ 30 ]. However, as our data also showed, there was great variability in the speed and scope of the responses to the impact of COVID-19 in the practices, indicating potentially variable standards and quality of care [ 31 ].…”
Section: Discussionsupporting
confidence: 75%
“…Other studies reported various organisational adjustments to separate infectious from non-infectious patients [ 4 ]. Mainly, this occurred at the level of individual practices [ 12 ]. In Slovenia, this occurred at the level of PCHCs and/or an administrative region level [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors create a highly uncertain operational environment for healthcare providers, which has been amplified during the Covid-19 pandemic, where healthcare systems around the world have had to adapt quickly by re-allocating care capacity to face the large numbers of patients battling Covid-19 (Rennert-May et al. , 2021; Stengel et al. , 2022).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Adding to this complexity is also healthcare managers' strong taskorientation with a low tolerance for mistakes (Tortorella et al, 2020). These factors create a highly uncertain operational environment for healthcare providers, which has been amplified during the Covid-19 pandemic, where healthcare systems around the world have had to adapt quickly by re-allocating care capacity to face the large numbers of patients battling Covid-19 (Rennert-May et al, 2021;Stengel et al, 2022). This reality has strengthened the call from scholars for research to investigate OM phenomena related to healthcare (Micheli et al, 2021).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%